The Host immuno-inflammatory response and intravascular volume replacement therapy in critically ill septic patients – are fluids a double-edged sword? - Djordjević, Dragan; Rondović, Goran; Udovičić, Ivo; Mladenović, Katarina; Zeba, Snježana (Vojnosanitetski pregled, 2026)
Intravascular volume replacement fluid therapy plays a pivotal role in the treatment of patients in circulatory shock. The interaction between various lines of therapy and immune response in critically ill septic patients remains a significant clinical challenge with no simple solution. Plasma expanders, crystalloids (such as physiological saline, balanced Ringer’s lactate, and Plasma-Lyte solution), and human albumin solution–the only acceptable colloid for critically ill patients–should be considered as necessary potent drugs with significant adverse effects. Sepsis is a very heterogeneous syndrome, with various magnitudes and persistence of inflammatory responses. Bearing in mind that the natural course of sepsis is highly complex, with phases of hyperinflammation and immunosuppression often occurring simultaneously in different locations, it is almost impossible to avoid the adverse effects of crystalloids, which are first-line intravascular volume-replacement solutions. Large-volume replacement therapy or rapid intravenous fluid infusion may induce shedding or partial denudation of the endothelial glycocalyx, thereby propagating tissue injury, leukocyte and platelet adhesion and activation. A compromised glycocalyx leads to detrimental capillary leak syndrome in sepsis. In clinical practice, serum albumin levels may indicate the timing and need to administer intravenous human albumin solution during fluid resuscitation when substantial volumes of crystalloids are required. This is an example of a “glycoprotective” fluid approach, with lower volumes and slower crystalloid infusion rates. The complex interaction among fluid therapy, the endothelium, the glycocalyx, and immune mediators is pathophysiologically relevant and very important for clinicians in therapeutic approaches.